El Modelo Gerencial Antioqueño: Taylorismo de Carriel y Camándula (2019)
This paper looks into a series of practices, traditions and values on which the antioqueño region, in Colombia, began to develop a process of economic development with some managerial particularities over the human factor. Such an argument tries to get to the suggestion of an Antioquenian model of management in a specific period of history.